1999
DOI: 10.1200/jco.1999.17.11.3512
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Doxorubicin and Conventionally Fractionated Radiotherapy in the Treatment of Locally Advanced Non–Small-Cell Lung Cancer and Head and Neck Cancer

Abstract: We conclude that combination of radiotherapy with Stealth liposomal doxorubicin is feasible. The potential role of such a regimen in the treatment of highly angiogenic tumors requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
107
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 27 publications
5
107
0
1
Order By: Relevance
“…Instant thin layer chromatography (ITLC) suggested an 80% labelling (Koukourakis et al, 1999), which is also a result found by Dr Laverman and colleagues. As additional more sophisticated analysis, performed by the later research group, failed to confirm this finding, it was suggested that the tumour and body imaging obtained in our studies is rather a result of 99m Tc-DTPA and not of labelled liposomes.…”
Section: Sirsupporting
confidence: 75%
See 4 more Smart Citations
“…Instant thin layer chromatography (ITLC) suggested an 80% labelling (Koukourakis et al, 1999), which is also a result found by Dr Laverman and colleagues. As additional more sophisticated analysis, performed by the later research group, failed to confirm this finding, it was suggested that the tumour and body imaging obtained in our studies is rather a result of 99m Tc-DTPA and not of labelled liposomes.…”
Section: Sirsupporting
confidence: 75%
“…The results presented by Koukourakis et al (1999Koukourakis et al ( , 2000a should therefore be interpreted with caution.…”
Section: Sirmentioning
confidence: 90%
See 3 more Smart Citations